A clinical study on maternal and fetal outcome in twin pregnancy at KIMS hospital, Hubli, Karnataka, India - Garag, Seeta Sunil; Raju D., Vinay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Development of two fetus inside the uterus is called twin gestation. Twin gestation is considered as high-risk pregnancy due to associated high maternal morbidity and perinatal mortality in comparison with singleton pregnancies. The past two decades have witnessed a sharp rise in the incidence of twin and higher order gestations. Methods: Prospective analytical study of all women admitted in Obstetrics and Gynaecology department with twin pregnancy at KIMS Hubli, over a period of one year between November 2016 and October 2017. Results: There were 11,127 deliveries occurred in study period of one year, out of which there were 174 twin deliveries accounting for 1.56% of prevalence rate. Anemia was the commonest complication occurring in 160 cases contributing around 90%. Preterm delivery was the second complication occurring in 124 cases accounting for 71%. Among 348 babies, there were 40 perinatal death accounting 11%. There was no maternal death. Conclusions: Twin pregnancy is a high-risk condition, should have mandatory hospital delivery. Early detection, proper treatment improves both maternal and neonatal outcome.